Information Experience of People with Visual Impairment on Audiobook Use as Information Sources - Toyibatul Nikmah; Heriyanto Heriyanto (D3 Perpustakaan Fakultas Vokasi Universitas Airlangga, 2022)
Background of the study: Information experience is a complex and multidimensional perpspective that sees the relationship between human and information. Purpose: The aim of the research is to understand the experience of person with visual impairment of Braille’iant Indonesia community when they use audiobook as information sources. Method: The research methods used was qualitative method, data collected using interview and informant were recruited through purposive sampling. Findings: Four themes emerged related to the information experience of people with visual impairment when using audiobook. The first theme is motivation which ilustrate the motivation to use audiobook, the second themes is awareness of people with visual impairment to choose information sources. The third one is access contraints that describe how they find obstacle to find the right information sources, the last theme is determining actions of participants to take actions after obtaining information from audiobook. Conclusion: The fourth theme shows information experience influenced by various factors and by the experience audiobook are not the main information sources used by participants.